Assessment of safety culture maturity in a food industry: a comparison between manufacturing and administration sector - Garcia, Drielly de Paula (2022)
Occupational safety and health are ongoing concerns for many organizations, especially for economic sectors that are leaders in work-related accidents, such as the food industry. An established safety culture is essential to support the development and successful progress of any safety management program. Therefore, monitoring the maturity of a company's safety culture is required for change planning and continuous improvement to ensure a safe workplace. This paper aims to assess the maturity degree of the safety culture of a multinational food industry, representing one of the segments with more occupational accidents in Brazil. An exploratory and descriptive research was developed, with a quantitative approach and based on a case study strategy. The manufacturing sector showed a mature safety culture, with a predominance of the sustainable level (58%), while the administration segment presented a high dispersion of data, incurring in a safety culture between the bureaucratic (23%), proactive (29%), and sustainable (33%) degrees. Safety at work was found to be associated with variables of different natures and the diagnosis carried out in this paper points out that the implementation of an organizational culture focused on safety requires a holistic view that goes beyond the technical aspects of the activity or the employees’ attributes, encompassing social and organizational elements, as well as the characteristics of each sector that must be considered by leaders for safety management to be effective